Viral etiology of life‐threatening pediatric pneumonia: A matched case‐control study. Issue 4 (8th April 2020) - Yu, Jianxing; Qian, Suyun; Liu, Chunyan; Xiao, Yan; Xu, Teng; Wang, Ying; Su, Hang; Chen, Lan; Yuan, Bin; Wang, Xinming; Xu, Baoping; Yang, Yan; et al.
Abstract: Background: Pediatric pneumonia remains a significant health challenge, while the viral risk factors for adverse outcomes in pediatric pneumonia are not yet fully clear. Methods: A matched case‐control study of pediatric patients with pneumonia was carried out in Beijing, China, between 2007 and 2015. The study enrolled 334 intensive care unit patients who developed life‐threatening diseases and 522 controls matched to the sex, age, ethnicity, admission dates, and residing district of the cases suffered from pneumonia. Nasopharyngeal aspirates were taken from all participants and tested by PCR for 18 common respiratory viruses. Results: At least, one virus was detected in 257 (77%) of the cases and 409 (78%) of the controls. We observed no difference in the prevalence of 17 respiratory viruses between cases and controls but found a higher frequency of influenza A virus (IFV‐A) in the cases than in the controls (7% vs 4%, P = .036). After adjusting for comorbid conditions and a history of reactive airway diseases, IFV‐A was associated with an increase in life‐threatening pneumonia (adjusted odds ratio = 2.55, 95% CI = 1.24‐5.24). Young age and congenital heart disease (aOR = 10.16‐10.27, P < .001) were also independent risk factors. Conclusions: The prevention of IFV infection is critical in decreasing the risk of life‐threatening pneumonia in children.